Would you mind if I get more? An experimental study of the envy game - Sandro Casal; Werner Güth; Mofei Jia; Matteo Ploner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
Envy is often the cause of mutually harmful outcomes. We experimentally study the impact of envy in a bargaining setting in which there is no conflict in material interests: a proposer, holding the role of residual claimant, chooses the size of the pie to be shared with a responder, whose share is exogenously fixed. Responders can accept or reject the proposal, with game types differing in the consequences of rejection: all four combinations of (not) self-harming and (not) other-harming are considered. We find that envy leads responders to reject high proposer claims, especially when rejection harms the proposer. Notwithstanding, maximal claims by proposers are predominant for all game types. This generates conflict and results in a considerable loss of efficiency.
Keywords: D63; D74; C91; C72; 330; social preferences; conflict; experimental economics; bargaining; Verhandlungstheorie; Nichtkooperatives Spiel; Konflikt; Soziale Wohlfahrtsfunktion; Test